2006 Rodocrosita -all about me- - Grupo Rodocrosita (2017)
Actúan: Alba Castillo, Americo Ferrari, Elena Gowland, Vicky Olivares, Sylvia Tavcar, Gabriela A. Tognetti, Alejandro Zingman | Iluminación: Lamberto Arévalo